(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
Ambon City is one of the cities in Maluku Province which has quite large fisheries potential. One of the potentials is to capture fisheries. Capture fisheries are activities that are highly dependent on the availability and carrying capacity of fish resources and the aquatic environment. Sustainability of fisheries requires appropriate management of fish resources, namely the use of fish resources by considering the sustainability of fish resources. However, the use of fishery resources has not been utilized optimally and sustainability has not been paid attention to, especially for small pelagic fish species. The aim of this research is to estimate the stock of small pelagic fish in the PPI Eri, Ambon City. Primary and secondary data collection at PPI Eri and surrounding areas. The data analysis used is data on catch and fishing effort including catch per unit effort (CPUE) and production surplus methods (sustainable potential (MSY) and fopt). The mini purse seine fishing fleet consists of boats, machines, nets, FADs and lights. Then the Flying Fish resource can continue to be utilized optimally and sustainably, ensuring that the production amount does not exceed the JTB limit (Amount of Allowable Catch), namely the JTB value is 222: 80 The JTB is 167 : 80 X 100% = 208.75 tons/year. Therefore, if the sustainable potential and optimum efforts are known, it is hoped that the Regional Maritime Affairs and Fisheries Service (Government) can apply the precautionary principle in managing fish resources in Maluku Province.